The Coevolution of Network Ties and Perceptions of Team Psychological Safety - Schulte, Mathis; Cohen, N. Andrew; Klein, Katherine J. (Organization Science, 2012)
Which comes first—team social networks or emergent team states (e.g., team climate)? We argue that team members' social network ties and team members' climate perceptions coevolve over time as a function of six reciprocal and co-occurring processes. We test our conceptual framework in a 10-month longitudinal study of perceptions of team psychological safety and social network ties in 69 work teams and find considerable support for our hypotheses. Our main results suggest that perceptions of psychological safety predict network ties. The more psychologically safe team members perceive their team to be, the more likely they are to ask their teammates for advice and to see them as friends, and the less likely they are to report difficult relationships with them. At the same time, network ties predict psychological safety. Team members adopt their friends' and advisors' perceptions of the team's psychological safety and reject the perceptions of those with whom they report a difficult relationship. Our framework and findings suggest that conceptual models and tests of unidirectional or team-level effects are likely to substantially misrepresent the mechanisms by which network ties and emergent team states coevolve.